2015
DOI: 10.4103/0971-6580.172286
|View full text |Cite
|
Sign up to set email alerts
|

Food color induced hepatotoxicity in Swiss albino rats, Rattus norvegicus

Abstract: Objective:Certain dietary constituents can induce toxicity and play a critical role in the development of several hepatic disorders. Tartrazine, metanil yellow and sunset yellow are widely used azo dyes in food products, so the present study is aimed to investigate the food color induced hepatotoxicity in Swiss albino rats.Materials and Methods:Swiss albino rats were divided into four groups, each group having six animals. Group I served as control, Group II, Group III and Group IV were administered with 25, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
8
24
0
1
Order By: Relevance
“…While the low dose of both tartrazine (15 mg/kg BW) and carmoisine (8 mg/kg BW) displayed a significant rise in the ALT and alkaline phosphatase activities, respectively as compared to the control rats (Amin et al, 2010). In addition, Saxena and Sharma (2015) reported that consumption of food color including tartrazine induces hepatic tissue damages in Swiss Albino Rats. These effects assessed through significant increased serum total protein, albumin, ALP and hepatic MDA level and significant lowered levels of SOD, reduced GSH and CAT in the hepatic tissue.…”
Section: Effect Of Food Azo Dyes On Liver Enzymes and Hepatotoxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…While the low dose of both tartrazine (15 mg/kg BW) and carmoisine (8 mg/kg BW) displayed a significant rise in the ALT and alkaline phosphatase activities, respectively as compared to the control rats (Amin et al, 2010). In addition, Saxena and Sharma (2015) reported that consumption of food color including tartrazine induces hepatic tissue damages in Swiss Albino Rats. These effects assessed through significant increased serum total protein, albumin, ALP and hepatic MDA level and significant lowered levels of SOD, reduced GSH and CAT in the hepatic tissue.…”
Section: Effect Of Food Azo Dyes On Liver Enzymes and Hepatotoxicitymentioning
confidence: 96%
“…In a recent study, tartrazine, a widely used synthetic azo dye, induced a sharp deficiency in the biomarkers of antioxidant (SOD, catalase and GSH) and a marked rise in MDA concentration in the brain cortex in comparison with the other groups of male rat pups (Mohamed et al, 2015;Saxena and Sharma, 2015).…”
Section: Effect Of Food Azo Dyes (Tartrazine and Carmoisin) On Lipid mentioning
confidence: 99%
“…In Manuscript to be reviewed who attributed similar changes in liver function to hepatocellular impairment. This liver damage would releases greater than normal levels of intracellular enzymes into the blood (Amin et al,2010;Himri et al, 2011;El-Wahab & Moram, 2015;Saxena &, Sharma, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Особливе місце серед актуа-льних проблем нефрології займає проблема ви-вчення факторів ризику розвитку та прогресування нефропатій. Визнано, що одна з вагомих екологіч-них причин високого рівня захворюваності нефро-патіями -це якість харчування [14].…”
Section: формування нефропатії при довготривалому вживанні харчового unclassified